Quality of life after Supracricoid Partial Laryngectomy - Marianne Yumi Nakai; Marcelo Benedito Menezes; Julia Vilas Boas Gonçalves de Carvalho; Lucas Porto Maurity Dias; Leandro Augusto de Barros Silva; Lucas Ribeiro Tenório; Antonio José Gonçalves (Journal of Otolaryngology - Head and Neck Surgery, 2021)
Abstract Background Supracricoid partial laryngectomy has good oncologic results in the treatment of advanced laryngeal cancer with the advantage of preserving larynx phonatory function when compared with total laryngectomy. However the rehabilitation could be a challenge, especially regarding swallowing function. Is supracricoid partial laryngectomy associated with better quality of life than total laryngectomy? Methods Survey study that included 33 patients (16 total laryngectomy and 17 supracricoid partial laryngectomy) with advanced larynx cancer surgically treated and fully rehabilitated. The quality of life were evaluated with EORTC QLQ C30 and H&N 35 instrument. Results Patients who underwent supracricoid partial laryngectomy obtained better scores in global health status-quality of life and general activities and had lower levels of sensory and speech-related symptoms. Conclusion SPL was associated with better quality of life when compared with TL. Graphical abstract